On-chip non-equilibrium dissociation curves and dissociation rate constants as methods to assess specificity of oligonucleotide probes - Wick, Lukas M. (Oxford University Press, 2006)
Nucleic acid hybridization serves as backbone for many high-throughput systems for detection, expression analysis, comparative genomics and re-sequencing. Specificity of hybridization between probes and intended targets is always critical. Approaches to ensure and evaluate specificity include use of mismatch probes, obtaining dissociation curves rather than single temperature hybridizations, and comparative hybridizations. In this study, we quantify effects of mismatch type and position on intensity of hybridization signals and provide a new approach based on dissociation rate constants to evaluate specificity of hybridized signals in complex target mixtures. Using an extensive set of 18mer oligonucleotide probes on an in situ synthesized biochip platform, we demonstrate that mismatches in the center of the probe are more discriminating than mismatches toward the extremities of the probe and mismatches toward the attached end are less discriminating than those toward the loose end. The observed destabilizing effect of a mismatch type agreed in general with predictions using the nearest neighbor model. Use of a new parameter, specific dissociation temperature (T(d-w), temperature of maximum specific dissociation rate constant), obtained from probe–target duplex dissociation profiles considerably improved the evaluation of specificity. These results have broad implications for hybridization data obtained from complex mixtures of nucleic acids.